Scheme for synchronous machine stator turn‐to‐turn protection. Issue 4 (3rd February 2020) - Platero, Carlos A.; Gyftakis, Konstantinos N.; Panagiotou, Panagiotis A.; Fernandez, Alba
Abstract : This study presents a new protection scheme for turn‐to‐turn fault protection in the stator windings of synchronous machines. The main difference with other methods is the calculation of voltage of the winding from the phase to ground and neutral to ground voltages, which can be obtained from the monitoring provided by any commercial generator multifunction protection relay. This new method allows the employment of the protection transformers already installed in the protection scheme, simplifying and reducing the cost of the protection function. To validate this new technique, finite element method simulations and numerous tests have been performed in a specially built synchronous generator with taps in one of the stator windings. In this way, several turn‐to‐turn faults have been created at different fault severity levels.